Financial Risk, Inflationary Trend and Financial Performance of Listed Deposit Money Banks in Nigeria: A Proposed Framework - Ramalan, Jibril; Kurfi, Aminu Kado; Mata, Bala Ado Kofar (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study proposed a framework on the moderating effect of inflationary trend on the relationship between financial risk and the financial performance of Nigeria listed deposit money banks. Literature has shown that financial risk parameters are very essential factors that adversely affect corporate firm financial performance. However, the main objective of this study is to propose a framework on the moderating effect of inflationary trends on the relationship between financial risk variables and financial performance of listed deposit money banks in Nigeria. The independent variable used in this study is financial risk proxy by credit risk, liquidity risk, market risk, operational risk and leverage risk. The moderating variable is inflationary trend measured as ratio of consumer price index (CPI) calculated as annual percentage changes in inflation rate and the dependent variable is financial performance measured by return on assets (ROA) and Tobin’s q. Therefore, based on the reviewed literatures a moderator is introduced to propose a framework for the study resulting from inconsistency in findings of previous studies. The study proposed capital asset pricing model as underpinning theory. As such, the study recommended for empirical investigation on the proposed research framework.